Analysis of Factors Affecting the Stock Price of Manufacturing Companies in the Food and Beverage Sub-Sector Listed on the IDX in 2020-2022 - Intan Puspita Rini; Dwi Muhammad Naufal; Muhammad Syahrul Kanji; Tiara Amelia Irawan; Esa Nurjannah (Syntax Idea)
The purpose of this journal is to investigate the influence of profitability and liquidity on the stock prices of manufacturing companies, particularly in the food and beverage subsector listed on the Indonesia Stock Exchange (IDX) during the period 2020-2022. The background of this journal stems from increased competition in the business world, prompting companies to adapt to avoid bankruptcy. One way to enhance capital is through the sale of stocks. The data sources for this journal are financial reports of manufacturing companies, specifically in the food and beverage subsector listed on the IDX from 2020 to 2022. The type of data used is secondary data derived from financial reports of companies in the food and beverage subsector listed on the IDX during the period 2020-2022, with a population consisting of 87 companies. The sampling method employed was purposive sampling, resulting in a total of 23 companies and 69 research samples from 2020 to 2022. This journal employs data analysis techniques including various regression analysis methods. Based on the research findings from various methodologies, it is found that profitability (Net Profit Margin) significantly influences stock prices. However, liquidity (Current Ratio) does not significantly affect food and beverage companies listed on the Indonesia Stock Exchange (IDX).